Managerialism implications on frontline Social Work Practices - Amaro, M. I.; F. Branco (European Journal of Social Work, 2019)
This paper analyses how social workers are affected by emerging technocratic phenomena at the workplace and how do they respond to it. The analysis will explore the challenges and limitations, but also the positive sides practitioners point out when reflecting about what is new in their professional performance and in the way they spend their professional time. The analysis is based on the gathering of 2 series of workload diaries from social workers, practicing in different contexts, and the conduction of focus groups with professionals to discuss the implications of what their working diaries show to their role as social workers. Results are discussed in the light of the de-professionalization thesis and of the New Public Management trends. The main findings point to diverse caseloads, depending on the type of institutional setting. In general, 45% of the working time is spent in Client-Related Activities, while 35% is attributed to System Information Management. Almost no time is spent on Professional Development (3%). More than a third of the working time is devoted to “paper work” activities. Only 26 % of the working time is spent in direct contact with clients’ activities. Despite this, in some professional discourses, over-bureaucratisation of practices in result of managerialist trends seems to be a worth-paying price for a “more technical” performance, recorded, monitored and easy to assess. The ambivalences implied by the ‘managerialist turn’ in professional experiences might be further explored in future research.